Two new species of Orgilus Haliday from the Russian Far East (Hymenoptera, Braconidae). Contributions to the knowledge of East Palaearctic insects (9). - Belokobylskij, Sergej A.; Taeger, Andreas (Beiträge zur Entomologie = Contributions to Entomology, 1998)
Orgilus fulvus sp. n. und Orgilus chankaicus sp. n. werden aus dem Fernen Osten Rußlands beschrieben. Stichwörter Orgilus, Hymenoptera, Braconidae, new species, Russian Far East, East Palaearctic. Nomenklatorische Handlungen chankaicus Belokobylskij & Taeger, 1998 (Orgilus), spec. n. fulvus Belokobylskij & Taeger, 1998 (Orgilus), spec. n.